Preparation method of semiconductor-grade high-purity quartz sand
Through chemical synthesis, sodium silicate reacts with strong acid cation exchange resin, combined with the secondary tandem resin column purification and calcining process, the problem of difficulty in preparing high-purity quartz sand by itself is solved in China, and low-cost, large-scale production is achieved Pure quartz sand, suitable for semiconductor applications.
Patent Information
- Application Number
- CN202411383316.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-03
AI Technical Summary
The existing technology relies on imported high-quality ores, making it difficult to prepare high-purity semiconductor-grade quartz sand in China, which limits the production of high-end quartz sand in China.
By chemical synthesis, the orthosilicate stock solution was obtained by ion exchange reaction between sodium silicate and strong acid cation exchange resin, and impurity separation aggregate was purified through a secondary tandem resin column, followed by aging and high-temperature calcination. Prepare high purity quartz sand.
It has achieved low-cost and large-scale production of high-purity quartz sand, which is suitable as the inner raw material of the quartz crucible for silicon growth in semiconductor single product. The detection value of impurity elements is lower than the standard, and the SiO2 content reaches 99.9999%, which is suitable for large-scale production.
Smart Images

Figure CN119240720A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ultra-high purity quartz sand preparation, and in particular to a method for preparing semiconductor-grade high-purity quartz sand. Background Art
[0002] At present, the mainstream production of high-purity quartz sand in the world adopts physical method to prepare quartz sand. For example, Unimin in the United States and TQC in Norway adopt physical crushing method of raw ore to prepare high-purity quartz sand. The physical method is very dependent on ore raw materials. At present, local companies in the United States and Norway have high-quality ore sources.
[0003] In order to break the dependence on imports of high-end quartz sand, our company invented a chemical synthesis method to prepare semiconductor-grade high-purity quartz sand. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing semiconductor-grade high-purity quartz sand, which can prepare high-purity quartz sand as the inner layer raw material of a quartz crucible for growing semiconductor single-piece silicon.
[0005] In order to achieve the above-mentioned object of the invention, the method for preparing semiconductor-grade high-purity quartz sand of the present invention adopts the following technical scheme:
[0006] (1) preparing an orthosilicic acid solution: using a sodium silicate solution and a strongly acidic cation exchange resin to undergo an ion exchange reaction to obtain an orthosilicic acid stock solution A;
[0007] (2) Purification of orthosilicic acid impurity separation aggregates: Orthosilicic acid stock solution A is purified by a secondary series resin column to obtain a high-purity orthosilicic acid solution B; the secondary series resin column includes a primary resin column and a secondary resin column, the primary resin column is filled with a chelating resin that can replace heavy metal ions with sodium ions, and the secondary resin column is filled with a hydrogen-type strong acid cation exchange resin that can thoroughly purify low-concentration alkali metal ions to less than 0.1 ppm;
[0008] (3) Aging and granulation: The orthosilicic acid solution B is concentrated, then aged until the solution is in the form of a gel, granulated and shaped by freezing and crystallizing, and then thawed and filtered to obtain quartz primary sand;
[0009] (4) Calcination modification: After acid washing and drying, the quartz sand is calcined at high temperature to obtain high-purity finished quartz sand.
[0010] Preferably, the specific operation of preparing orthosilicic acid in step (1) is as follows:
[0011] 1.1) Resin pretreatment: Fill the ion exchange resin column with a strong acidic cation exchange resin, and then use 2.5-5 times the volume of the resin to regenerate the resin with a 4-8%wt acidic solution. After the resin column is regenerated, rinse it with EDI ultrapure water until the pH value is neutral for use;
[0012] 1.2) dissolving sodium silicate nonahydrate solid in EDI ultrapure water to prepare a sodium silicate solution with a mass concentration of 5-15%;
[0013] 1.3) The sodium silicate solution is passed through an ion exchange resin filter column to be used to generate an ion exchange reaction. The volume ratio of the strong acid cation exchange resin to the sodium silicate solution is 1:0.8-1.8. The equation for the ion exchange reaction is: Na2SiO3+HM→H2SiO3+Na-M.
[0014] Preferably, the specific operation of purifying the orthosilicic acid impurity separation aggregate in step (2) is as follows:
[0015] 2.1) Pretreatment of the primary resin column: first, backwash with a saturated sodium chloride solution of one times the volume of the resin, then backwash with a 5%wt sodium hydroxide solution of 2-3 times the volume of the resin, and finally forward wash with EDI ultrapure water until neutral for use;
[0016] 2.2) Pretreatment of the secondary resin column: first backwash with 5-8% wt hydrochloric acid at 2-4 times the volume of the resin, and then forward rinse with EDI ultrapure water until it becomes neutral for use;
[0017] 2.3) The orthosilicic acid stock solution A is passed through a standby primary resin column to remove heavy metal ions, and then passed through a standby secondary resin column to remove alkali metal ions to obtain a high-purity orthosilicic acid solution B.
[0018] Preferably, in step (3), the orthosilicic acid solution B is heated to 50-60° C. and then concentrated by negative pressure distillation. After concentration, the mass concentration of the orthosilicic acid solution B is 20-30%.
[0019] Preferably, the temperature of the frozen crystallization in step (3) is below -15°C and the freezing time is more than 15 hours.
[0020] Preferably, the aging temperature in step (3) is 50-80° C., and the aging time is 1-5 h.
[0021] Preferably, the acid washing method of the quartz quartz sand in step (4) is as follows: first, wash it with EDI ultrapure water, then discharge it into an acid washing tank, soak it with 3-5% hydrochloric acid for 0.5-2h with stirring to wash away the residue on the surface of the quartz quartz sand, filter and separate the acid liquid, and then wash away the residual acid liquid with pure water to obtain clean quartz quartz sand.
[0022] Preferably, in step (4), the calcination temperature is 1100° C.-1300° C., and the calcination time is 2-5 h.
[0023] Preferably, the diameter of the finished quartz sand obtained in step (4) is 50-200 μm.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] The invention adopts low-cost sodium silicate as a silicon source, firstly undergoes an ion exchange reaction with a strong acid cation exchange resin to obtain an orthosilicic acid stock solution A, then performs impurity separation and aggregation purification on the orthosilicic acid stock solution, removes heavy metal ions by filling a primary resin column with a chelating resin, and then removes alkali metal ions and alkali metals by filling a secondary resin column with a hydrogen-type strong acid cation exchange resin, thereby obtaining a high-purity orthosilicic acid solution B, and then performs aging and granulation for preliminary shaping, performs ultra-low temperature freezing crystallization to prepare clean silicon dioxide, and then performs acid washing and calcination modification to prepare high-purity quartz sand, which can be used as an inner layer raw material of a quartz crucible for growing semiconductor single silicon. The invention optimizes the process steps, adopts a secondary series resin column to perform impurity separation and purification on the orthosilicic acid stock solution A, removes impurities, and uses low-cost sodium silicate as a silicon source to prepare high-purity quartz sand, which is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 is an optical microscope image of the thawed crystals in Example 1;
[0027] Figure 2 This is an optical microscope image of the quartz sand after pickling in Example 1;
[0028] Figure 3 This is a test result diagram of X-ray diffraction detection of the finished quartz sand prepared in Example 1;
[0029] Figure 4 This is an optical microscope image of the crystals after thawing in Example 2. DETAILED DESCRIPTION
[0030] The present invention is further explained below in conjunction with specific implementation methods. It should be understood that these implementation methods are only used to illustrate the present invention and are not used to limit the scope of the present invention. After reading the present invention, various equivalent forms of modifications to the present invention by those skilled in the art all fall within the scope defined by the claims attached to this application.
[0031] Example 1
[0032] (1) Pretreatment of 001*7 hydrogen type cation exchange resin: 001*7 hydrogen type cation exchange resin is first soaked in a saturated NaCl solution. 1L of the resin is placed in a 2L saturated NaCl solution and soaked for 18-20 hours. Then the NaCl solution is drained and rinsed with EDI ultrapure water until the discharged water has no strange color. The resin is filled into a cylindrical ion exchange resin filter column with a diameter of 3cm and a length of 1.6m. The filling height is about 1.45m. Then the ion exchange resin filter column is rinsed with 1L 4%wt NaOH solution. Then, the ion exchange resin filter column is rinsed with 2LEDI ultrapure water. The discharged water is close to neutral. Then, 2.5L 8%wt HCL solution is used at a flow rate of 180ml / min to rinse the regenerated ion exchange resin filter column. Finally, it is rinsed with about 4L EDI ultrapure water until it is neutral for use.
[0033] Take 236g of sodium silicate nonahydrate solid and add 800mL of high-purity water, stir and dissolve for 30min to obtain 1L of sodium silicate solution with a weight of about 10%, and then use a 450nm microporous filter membrane for negative pressure filtration. After filtration, the filtrate is clear and transparent without solid suspension and precipitation. Then, the filtrate is pumped into the above-mentioned ion exchange resin filter column for use by a peristaltic pump at a flow rate of about 180mL / min. After 150mL of water is discharged from the ion exchange resin filter column, the water discharge will stop. Take a new container to collect and discharge 800mL of orthosilicic acid stock solution A for use;
[0034] (2) Pretreatment of CH-90Na chelating resin: CH-90Na chelating resin is also used to soak with saturated NaCl solution. 300mL of resin is placed in 600mL of saturated NaCl solution and soaked for 18-20 hours. Then, the NaCl solution is discharged and rinsed with clean water. The resin is filled into a 2cm diameter cylindrical primary resin column of 1.2m in length, and the filling height is about 95cm. Then, the resin column is rinsed with 300mL of 4%wt HCL solution, and then the resin is rinsed with 500mL of pure water, and the discharged water is close to neutrality. Then, 1L of 5%wt NaOH solution is used to rinse the regenerated resin column with a flow velocity of 120ml / min, and finally, about 1.5L of EDI ultrapure water is used for standby use until neutrality.
[0035] Pretreatment of 732 hydrogen-type strong acid cation exchange resin: 732 hydrogen-type strong acid cation exchange resin is the same as above. First, soak it in saturated NaCl solution. Place 300mL of resin in 600mL saturated NaCl solution and soak for 18-20 hours. Then drain the NaCl solution and rinse it with clean water so that the discharged water has no strange color. Fill the resin into a cylindrical secondary resin column with a diameter of 2cm and a length of 1.2m. The filling height is about 95cm. Then rinse the resin column with 300mL 4%wt NaOH solution, and then rinse the resin column with 500mL pure water. The discharged water is close to neutral. Then rinse the regenerated resin column with 1L 5%wt HCL solution at a flow rate of 120ml / min, and finally rinse it with about 1.5L EDI ultrapure water until it is neutral for use.
[0036] 800 mL of the orthosilicic acid stock solution to be used in step (1) is passed through the primary resin column and the secondary resin column at a flow rate of 120 mL / min, and about 700 mL of the second half of the leaching liquid is collected to obtain a high-purity orthosilicic acid solution B;
[0037] (3) The high-purity orthosilicic acid solution was transferred into a three-hole flask, and then transferred into a water bath for heating at 65°C. A 2KPa negative pressure vacuum pump and a condenser were connected to the supporting negative pressure distillation equipment, and the negative pressure distillation was performed for 1 hour. After the sample was concentrated to about 300 mL, it was transferred into a plastic beaker and continued to be kept in a water bath for 1.5 hours. At this time, the solution in the beaker was in the form of a viscous jelly. The beaker was transferred into a refrigerator, rapidly frozen to 0°C, and then slowly cooled to -25°C. The low-temperature freezing was maintained for 16 hours, and then taken out and thawed at room temperature. After complete thawing, the lower layer of the solution was sampled and observed as shown in Figure (1). The crystal morphology and size were uneven. The thawed slurry was then filtered with a 200-mesh filter to remove the broken crystals and the solution, and large-grained quartz quartz sand was obtained.
[0038] (4) Rinse the large crystals in the filter screen with EDI ultrapure water, then transfer the crystals to a beaker, use 300mL 5%wt hydrochloric acid to stir and soak for 1h, then soak for 1h with ultrasonic oscillation, filter out the hydrochloric acid and rinse with EDI ultrapure water to remove the residual acid, transfer to a watch glass, put it in an 80℃ constant temperature drying oven to dry for 2h, take a sample for microscopic observation as shown in Figure (2); then put the dried crystals into a crucible, send it into a muffle furnace, set the temperature control to 20℃ / min to 700℃, 10℃ / min to 1000℃, 5℃ / min to 1300℃, keep it at 1300℃ for 2.5h, then cool it naturally to room temperature to obtain a high-purity sample quartz sand, and take a sample for X-ray diffraction detection (XRD). The test result is shown in Figure (3). The diffraction angle corresponding to the strong peak is compared with the database, and the crystal form overlaps with the α-quartz crystal form. Therefore, the prepared quartz sand is an α-quartz crystal form.
[0039] According to the 17 impurity elements in the group standard T / CEMIA024-2021 "Quartz Stack Production Specifications for Semiconductor Single Crystal Silicon Growth", the prepared quartz sand samples were tested by ICP-MS, and the results are as follows (in ppm):
[0040] Mn: 0.008; Al: 0.09; Ca: 0.011; Mg: 0.007; Ba: 0.009; Cr; 0.006; Cu: 0.005; Fe: 0.04; Ni : 0.007; Li: 0.007; Na: 0.04; K: 0.01; Zr: 0.005; Ti: 0.017; Ge: 0.004; P: 0.019; B: 0.02.
[0041] The above impurity test results show that not only are the detection values of the 17 impurity elements lower than the impurity values in the standard inner layer synthetic raw material quartz sand, but the sum of the contents of the 17 impurity oxides is less than 1ppm, concluding that the SiO2 content is ≥99.9999%.
[0042] Example 2
[0043] (1) Regeneration of 001*7 hydrogen-type cation exchange resin: Example 1: After use, the resin column was rinsed with 1L of 4%wt NaOH solution to wash away the residual sodium silicate solution and the silicate sol adsorbed on the resin layer. Then, the ion exchange resin filter column was rinsed with 2L of EDI ultrapure water, and the discharged water was nearly neutral. Then, 2.5L of 8%wt HCL solution was used at a flow rate of 180ml / min to rinse the regenerated ion exchange resin filter column. Finally, about 4L of EDI ultrapure water was used to rinse until it was neutral for use.
[0044] Take 118g of sodium silicate nonahydrate solid and add it to 900mL of high-purity water, stir and dissolve for 30min to obtain 1L of sodium silicate solution with a weight of about 5%, and then use a 450nm microporous filter membrane for negative pressure filtration. After filtration, the filtrate is clear and transparent without solid suspension and precipitation. Then, the filtrate is pumped into the above-mentioned ion exchange resin filter column for use by a peristaltic pump at a flow rate of about 180mL / min. After 150mL of water is discharged from the ion exchange resin filter column, the water discharge will stop. Take a new container to collect and discharge 800mL of orthosilicic acid stock solution A for use;
[0045] (2) Regeneration of CH-90Na chelating resin: The resin column after use in Example 1 was rinsed with 1L of 5%wt NaOH solution at a flow rate of 120ml / min to regenerate the resin column, and finally rinsed with about 1.5L of pure water until it was neutral for use;
[0046] Regeneration of 732 hydrogen-type strongly acidic cation exchange resin: Example 1: The used resin column was rinsed with 1L of 5%wt HCL solution at a flow rate of 120ml / min to regenerate the resin column, and finally rinsed with about 1.5L of EDI ultrapure water until it was neutral for use;
[0047] 800 mL of the orthosilicic acid stock solution to be used in step (1) is passed through the primary resin column and the secondary resin column at a flow rate of 120 mL / min, and about 700 mL of the second half of the leaching liquid is collected to obtain a high-purity orthosilicic acid solution B;
[0048] (3) The high-purity orthosilicic acid solution was transferred into a three-hole flask, and then transferred into a water bath for heating at 65°C. A 2KPa negative pressure vacuum pump and a condenser were connected to the supporting negative pressure distillation equipment, and the negative pressure distillation was performed for 1 hour. After the sample was concentrated to about 300 mL, it was transferred into a plastic beaker and continued to be kept in a water bath for 5 hours. At this time, the solution in the beaker was in the form of a viscous jelly. The beaker was transferred into a refrigerator, rapidly frozen to 0°C, and then slowly cooled to -25°C. The low-temperature freezing was maintained for 16 hours, and then taken out and thawed at room temperature. After complete thawing, the lower layer of precipitation was removed for microscopic observation as shown in Figure (4). The thawed slurry was filtered with a 200-mesh filter to filter out the broken crystals and solution to obtain large-grained quartz primary sand.
[0049] (4) Rinse the large crystals in the filter with EDI ultrapure water, then transfer the crystals to a beaker, use 300mL 5%wt hydrochloric acid to stir and soak for 1h, then soak for 1h with ultrasonic oscillation, filter out the hydrochloric acid and rinse with high-purity water to remove the residual acid, transfer to a watch glass, and dry in a constant temperature drying oven at 80℃ for 2h; then put the dried crystals into a crucible, send it into a muffle furnace, set the temperature control to 20℃ / min to 700℃, 10℃ / min to 1000℃, 5℃ / min to 1300℃, keep it at 1300℃ for 2.5h, and then cool it naturally to room temperature to obtain a high-purity sample quartz sand. The sample meets the standards after XRD and ICP-MS.
[0050] Example 3
[0051] (1) Regeneration of 001*7 hydrogen-type cation exchange resin: As in Example 2, the used resin column was rinsed with 1L of 4%wt NaOH solution to wash away the residual sodium silicate solution and the silicate sol adsorbed on the resin layer, and then the ion exchange resin filter column was rinsed with 2L of EDI ultrapure water, and the discharged water was nearly neutral; then 2.5L of 8%wt HCL solution was used at a flow rate of 180ml / min to rinse the regenerated ion exchange resin filter column, and finally rinsed with about 4L of EDI ultrapure water until it was neutral for use;
[0052] Take 354g of sodium silicate nonahydrate solid and add 750mL of high-purity water, stir and dissolve for 30min to obtain 1L of sodium silicate solution with a weight of about 15%, and then use a 450nm microporous filter membrane for negative pressure filtration. After filtration, the filtrate is clear and transparent without solid suspension and precipitation. Then, the filtrate is pumped into the above-mentioned ion exchange resin filter column for use by a peristaltic pump at a flow rate of about 180mL / min. When ion exchange occurs, the resin column generates a lot of heat, and the peristaltic pump flow rate is increased to 120ml / min, and finally reduced to 80ml / min. After collection, 800mL of orthosilicic acid stock solution A is discharged for use;
[0053] (2) Regeneration of CH-90Na chelating resin: As in Example 2, the used resin column was rinsed with 1L 5%wt NaOH solution at a flow rate of 120ml / min to regenerate the resin column, and finally rinsed with about 1.5L EDI ultrapure water until it was neutral for use;
[0054] Regeneration of 732 hydrogen-type strongly acidic cation exchange resin: Same as in Example 2, the used resin column was rinsed with 1L 5%wt HCL solution at a flow rate of 120ml / min to regenerate the resin column, and finally rinsed with about 1.5L EDI ultrapure water until it was neutral for use;
[0055] Passing 800 mL of the orthosilicic acid stock solution to be used in step (1) through the primary resin column and the secondary resin column at a flow rate of 80 mL / min, respectively, collecting about 700 mL of the second half of the leaching liquid to obtain a high-purity orthosilicic acid solution B;
[0056] (3) The high-purity orthosilicic acid solution was transferred into a three-hole flask, and then transferred into a water bath for heating at 65° C., and connected to a 2KPa negative pressure vacuum pump and a condenser and other supporting negative pressure distillation equipment, and the negative pressure distillation was performed for 40 minutes. After the sample was concentrated to about 500 mL, it was transferred into a plastic beaker and continued to be kept warm in a water bath for 0.5 hours. At this time, the solution gel in the beaker was in a viscous jelly state. The beaker was transferred into a refrigerator, rapidly frozen to 0° C., and then slowly cooled to -25° C., and kept frozen at low temperature for 16 hours, and then taken out and thawed at room temperature. After complete thawing, the lower layer of precipitation was taken out for microscopic observation. The proportion of broken crystals was not much different from that in Example 1. The thawed slurry was filtered with a 200-mesh filter to filter out the broken crystals and solution to obtain large-particle crystalline quartz primary sand;
[0057] (4) Rinse the large crystals in the filter with EDI ultrapure water, then transfer the crystals to a beaker, use 300mL 5%wt hydrochloric acid to stir and soak for 1h, then soak for 1h with ultrasonic oscillation, filter out the hydrochloric acid and rinse with EDI ultrapure water to wash away the residual acid, transfer to a watch glass, and dry in a constant temperature drying oven at 80℃ for 2h; then put the dried crystals into a crucible, send it into a muffle furnace, set the temperature control to 20℃ / min to 700℃, 10℃ / min to 1000℃, 5℃ / min to 1300℃, keep it at 1300℃ for 2.5h, and then cool it naturally to room temperature to obtain a high-purity sample quartz sand. The sample meets the standards after XRD and ICP-MS detection.
Claims
1. A method for preparing semiconductor-grade high-purity quartz sand, characterized in that: The steps include: (1) Preparation of orthosilicic acid: using a sodium silicate solution and a strongly acidic cation exchange resin to undergo an ion exchange reaction to obtain an orthosilicic acid stock solution A; (2) Purification of orthosilicic acid impurity separation aggregates: orthosilicic acid stock solution A is purified by a secondary series resin column to obtain a high-purity orthosilicic acid solution B; the secondary series resin column includes a primary resin column and a secondary resin column, the primary resin column is filled with a chelating resin, and the secondary resin column is filled with a hydrogen-type strong acid resin; (3) Aging and granulation: The orthosilicic acid solution B is concentrated and then aged until the solution is in a gel state, and granulated and shaped by freezing and crystallization, and then thawed and filtered to obtain quartz primary sand; (4) Calcination modification: After acid washing and drying, the quartz sand is calcined at high temperature to obtain high-purity finished quartz sand.
2. The method for preparing semiconductor-grade high-purity quartz sand according to claim 1, characterized in that: The specific operation of preparing orthosilicic acid in step (1) is as follows: 1.1) Resin pretreatment: Fill the ion exchange resin column with a strong acidic cation exchange resin, and then use 2.5-5 times the volume of the resin to regenerate the resin with a 4-8%wt acidic solution. After the resin column is regenerated, rinse it with EDI ultrapure water until the pH value is neutral for use; 1.2) dissolving sodium silicate nonahydrate solid in EDI ultrapure water to prepare a sodium silicate solution with a mass concentration of 5-15%; 1.3) The sodium silicate solution is passed through an ion exchange resin filter column to be used to generate an ion exchange reaction, and the volume ratio of the strong acid cation exchange resin to the sodium silicate solution is 1:0.8-1.
8.
3. The method for preparing semiconductor-grade high-purity quartz sand according to claim 1, characterized in that: The specific operation of purifying the orthosilicic acid impurity separation aggregate in step (2) is as follows: 2.1) Pretreatment of the primary resin column: first, backwash with a saturated sodium chloride solution of one times the volume of the resin, then backwash with a 5%wt sodium hydroxide solution of 2-3 times the volume of the resin, and finally forward wash with EDI ultrapure water until neutral for use; 2.2) Pretreatment of the secondary resin column: first backwash with 5-8% wt hydrochloric acid at 2-4 times the volume of the resin, and then forward rinse with EDI ultrapure water until it becomes neutral for use; 2.3) The orthosilicic acid stock solution A is passed through a standby primary resin column to remove heavy metal ions, and then passed through a standby secondary resin column to remove alkali metal ions to obtain a high-purity orthosilicic acid solution B.
4. The method for preparing semiconductor-grade high-purity quartz sand according to claim 1, characterized in that: In step (3), the orthosilicic acid solution B is heated to 50-60° C. and then concentrated by negative pressure distillation. After concentration, the mass concentration of the orthosilicic acid solution B is 20-30%.
5. The method for preparing semiconductor-grade high-purity quartz sand according to claim 1, characterized in that: The temperature of the frozen crystallization in step (3) is below -15°C and the freezing time is more than 15 hours.
6. The method for preparing semiconductor-grade high-purity quartz sand according to claim 1, characterized in that: The aging temperature in step (3) is 50-80° C. and the aging time is 1-5 h.
7. The method for preparing semiconductor-grade high-purity quartz sand according to claim 1, characterized in that: The pickling method of the quartz quartz sand in step (4) is as follows: first, it is washed with EDI ultrapure water, then discharged into a pickling tank, and stirred and soaked with 3-5% hydrochloric acid for 0.5-2h to wash away the residue on the surface of the quartz quartz sand, and the acid solution is separated by filtration, and then the residual acid solution is washed with EDI ultrapure water to obtain clean quartz quartz sand.
8. The method for preparing semiconductor-grade high-purity quartz sand according to claim 1, characterized in that: In step (4), the calcination temperature is 1100° C.-1300° C., and the calcination time is 2-5 hours.
9. The method for preparing semiconductor-grade high-purity quartz sand according to claim 1, characterized in that: The diameter of the finished quartz sand obtained in step (4) is 50-200 μm.
